Vulnerability of the role of women in disaster management based on preparedness, response, and recovery phases - Galleto, Patrick G.; Campiseño, Evelyn R. (2015)
The role of women in disaster management is currently underdeveloped in Zamboanga del Norte. This may be due to failure of women to get involve in disaster management particularly recognizing their significant role in the preparedness, response, and recovery phases. This study was conducted to determine the vulnerability of the role of women in disaster management based on preparedness, response, and recovery phases in Zamboanga del Norte, Dipolog and Dapitan Cities. Descriptive survey method of research was employed with the aid of questionnaire checklist which was administered to 373 members of the Local Women Organizations in the province. The study revealed that role of women in disaster management was intensely vulnerable in the areas along preparedness, response, and recovery phases. The necessities that enhancement along preparedness phase is needed, more focus and understanding of the response phase is imperative, and redefining role during recovery period must be enforced to reduce vulnerability and build resilience of the role of women in the province
Keywords: Emergency management; Mindanao studies; Women in disaster management